PENGARUH ASIMETRI INFORMASI, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2014 - Azari, T. M Rizki; Facrizal, Facrizal (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
The objectives of the research are to examine the effect of the information asymmetry, profitability, and leverage on the firm value both simultaneously and partially. In this research the firm value using price to book value as the proxy. Data obtained from the financial statements and annual reports of manufacturing companies that listed in the Indonesia Stock Exchange. Research conduct in 4 years (2012-2014). By using purposive sampling, there are 35 companies fulfilling the sample criteria of the sample. Multiple linear regression was used to test the hypothesis. The results of this research are information asymmetry, profitability, and leverage simultaneously affect on the firm value. Information asymmetry not partially affect on the firm value. Profitability partially affect on the firm value. Leverage partially affect on the firm value.Keywords: information asymmetry, profitability, leverage, firm value, price to book value